SOSIALISASI DAN PRAKTEK PEMBUATAN LAPORAN KEUANGAN SEDERHANA UNTUK UMKM DI KELURAHAN TIDUNG, KEPULAUAN SERIBU: Socialization and Practice of Making Simple Financial Reports for MSMEs in Tidung Village, Seribu Islands - Yulianto , Kampono Imam; Damayanty, Prisila; Nurdiana , Diah; Rahmadi, Zara Tania; Istiqomah , Rulyannas Tasya (ASOSIASI IDEBAHASA KEPRI, 2024)
This research aims to analyze the socialization process and practice of making simple financial reports for micro, small and medium enterprises (MSMEs) in Tidung Village, Seribu Islands. The method used is a case study with a qualitative approach. Data was collected through in-depth interviews with MSME owners and financial managers as well as direct observation of the practice of preparing financial reports. The research results show that intensive socialization and the practice of making simple financial reports provide significant benefits for MSMEs in improving their financial understanding and skills.